CeMn-C catalyst with dual moisture-proof protection as well as preparation method and application of CeMn-C catalyst

By using carbon material support and specific treatments in manganese and cerium composite oxide catalysts to generate CeMn@C catalysts rich in grain boundaries, the problem of reduced activity of the catalyst in high humidity environment is solved, and efficient and stable decomposition of ozone within the entire humidity range is achieved. effect.

CN119259027APending Publication Date: 2025-01-07SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310831036.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing manganese and cerium composite oxide catalysts have poor ozone decomposition effects in high humidity environments, lack humidity resistance, and cannot maintain catalytic activity for a long time under high humidity conditions.

Method used

Using carbon material as a support, the rich grain boundaries of amorphous MnO2 and CeO2 are generated by immersion and calcination of KMnO4 and cerium salt, forming a CeMn@C catalyst with dual moisture resistance protection, controlling the generation order and position of MnO2 and CeO2. , provides a hydrophobic reaction environment and reduces competitive adsorption of water molecules at active sites.

Benefits of technology

Maintain more than 90% of the ozone decomposition activity within the entire humidity range (RH=0%~95%), which significantly improves the moisture resistance and stability of the catalyst and ensures efficient ozone decomposition performance in high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259027A_ABST
    Figure CN119259027A_ABST
Patent Text Reader

Abstract

The invention discloses a CeMn-C catalyst with dual moisture-proof protection as well as a preparation method and application of the CeMn-C catalyst. The preparation method of the CeMn-C catalyst comprises the following steps: firstly, dipping a carbon carrier in a mixed solution of KMnO4 and cerium salt, fully reacting, and then drying and removing water to obtain a catalyst precursor; and then carrying out calcination treatment for 0.5-24 hours in an air atmosphere under the condition of 200-400 DEG C, so as to obtain the CeMn-C catalyst with dual moisture-proof protection. Wherein the catalyst precursor comprises a manganese-cerium active component and a carbon carrier, and the mass ratio of the manganese-cerium active component to the carbon carrier is 1: (2-30); the manganese-cerium active component is composed of amorphous MnO2 and Ce < 2 + > according to a mass ratio of (1-10): 1. According to the catalyst, moisture-resistant oxygen vacancies are generated through rich grain boundaries of MnO2-CeO2, so that competitive adsorption and accumulation of water molecules on the catalyst can be reduced to the greatest extent, and the catalyst can efficiently and stably decompose ozone in a high-humidity environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal oxide catalysts, and more specifically, to a CeMn@C catalyst with double moisture-resistant protection, a preparation method and an application thereof. Background Art

[0002] In recent years, ozone pollution has become one of the most serious hazards in the world, posing a huge threat to human health and ecosystems. With the rapid development of modernization, VOCs and NOx emitted by factories and motor vehicles have increased the amount of O in the atmosphere through photochemical reactions. 3 At the same time, residual O caused by air disinfection, chemical synthesis, water purification and flue gas desulfurization 3 Further exacerbating the 3 Ozone is highly oxidizing and irritating. Long-term exposure to low concentrations of O 3 It can also cause serious cardiopulmonary, respiratory and cardiovascular diseases. 3 It will also seriously inhibit the growth and development of plants, resulting in a 20% or more reduction in crop yields each year. Therefore, eliminating ozone pollution has important practical significance for the protection of the global environment and ecosystem.

[0003] At present, among the many ozone removal methods, catalytic decomposition is the most popular method because it can 3 Catalytic decomposition into O at room temperature 2 , high efficiency, safety and no energy consumption make it the most widely used O 3 Treatment method. The catalysts used in the catalytic decomposition method mainly include supported catalysts and metal oxide catalysts, wherein supported catalysts generally refer to catalysts obtained by loading active components onto a carrier with a stable structure and a high specific surface area. For example, the prior art discloses an ozone decomposition catalyst and a preparation method thereof. The ozone decomposition catalyst includes 30wt.% to 60wt.% of nano-aluminum sol and 40wt.% to 70wt.% of manganese-cerium composite oxide loaded on the aluminum sol. It can decompose ozone for a long time at room temperature, but its catalytic efficiency is greatly affected by the ambient humidity. It can only work in an environment with a relative humidity of no more than 35%. When the relative humidity of the air is high, water molecules will compete with ozone molecules for adsorption at the active sites, causing the catalyst to deactivate quickly. Therefore, the moisture resistance of existing ozone decomposition catalysts needs to be further improved. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects and shortcomings of the existing manganese-cerium composite oxide catalyst in a high humidity environment, that is, the poor ozone decomposition effect, and to provide a method for preparing a CeMn@C catalyst with dual moisture-resistant protection.

[0005] Another object of the present invention is to provide a CeMn@C catalyst having dual moisture resistance protection.

[0006] Another object of the present invention is to provide a CeMn@C catalyst with double moisture resistance protection for use in decomposing ozone.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] The present invention provides a method for preparing a CeMn@C catalyst with dual moisture-resistant protection, which specifically comprises the following steps:

[0009] S1. Impregnation of carbon support with KMnO 4 and a cerium salt in a mixed solution, and after sufficient reaction, drying and removing water to obtain a catalyst precursor;

[0010] S2. The catalyst precursor in S1 is calcined in an air atmosphere to obtain a CeMn@C catalyst having dual moisture-resistant protection;

[0011] The catalyst precursor in S1 includes a manganese cerium active component and a carbon carrier, and the mass ratio of the manganese cerium active component to the carbon carrier is 1:(2-30); the manganese cerium active component is amorphous MnO 2 and Ce 2+ Composition according to mass ratio (1-10):1;

[0012] The calcination temperature in S2 is 200-400° C., and the calcination time is 0.5-24 h.

[0013] The present invention uses carbon material as a carrier and MnO 4 - The reaction generates amorphous MnO 2 , and Ce 2+ Adsorbed on the carbon material, and then calcined under specific conditions, by controlling the MnO 2 and CeO 2 The generation order and position of carbon materials are MnO 2 While providing a hydrophobic reaction environment, MnO 2 -CeO 2 The rich grain boundaries produce moisture-resistant oxygen vacancies, which minimize the competitive adsorption and accumulation of water molecules at the active sites of the catalyst, allowing the catalyst to decompose ozone efficiently and stably in a high humidity environment.

[0014] The study found that MnO 2 and CeO 2 The formation process of the catalyst is crucial to the catalytic performance of the catalyst. Only when a specific ratio of manganese and cerium active components are simultaneously loaded on the carbon material can a catalyst with moisture-resistant oxygen vacancies be obtained.2 Reload CeO 2 , or load CeO first 2 Reload MnO 2 , the active sites will be covered, and the catalytic activity and stability obtained are poor. Moreover, when the amorphous MnO 2 If the ratio is too large or too small, only MnO can be obtained after calcination. 2 Crystalline or CeO alone 2 Crystal form, unable to form two grain boundaries (MnO 2 -CeO 2 ), nor can it produce moisture-resistant oxygen vacancies, which leads to poor ozone catalytic decomposition performance of the catalyst. In addition, too high a calcination temperature will cause MnO 2 Transformed into Mn 2 O 3 If the calcination time is too short, the grain boundary cannot be completely formed. That is, the temperature and time of the calcination treatment will affect the catalytic activity and moisture resistance of the CeMn@C catalyst.

[0015] Preferably, the catalyst precursor in S1 comprises a manganese-cerium active component and a carbon support, and the mass ratio of the manganese-cerium active component to the carbon support is 1:(5-20); the amorphous MnO 2 and Ce 2+ The mass ratio of the manganese cerium active component to the carbon support is (3-6):1. Specifically, the mass ratio of the manganese cerium active component to the carbon support is 1:20, and the amorphous MnO 2 and Ce 2+ The mass ratio of the manganese cerium active component to the carbon support is 6:1; or, the mass ratio of the manganese cerium active component to the carbon support is 1:5, and the amorphous MnO 2 and Ce 2+ The mass ratio is 3:1.

[0016] Preferably, the calcination temperature in step S2 is 250-350°C, and the calcination time is 2-6 hours. Optionally, the calcination temperature and time are 350°C and 2 hours; or, the calcination temperature and time are 250°C and 6 hours.

[0017] Specifically, KMnO in the mixed solution in step S1 4 The concentration of KMnO is 0.05-1 mol / L, and the concentration of cerium salt is 0.01-0.1 mol / L. 4 The concentration of is 0.05mol / L and 1mol / L; the concentration of cerium salt is 0.01mol / L, 0.05mol / L and 0.1mol / L.

[0018] Optionally, the carbon carrier in step S1 is at least one of activated carbon, carbon nanotubes and graphene.

[0019] Specifically, the cerium salt in step S1 is a divalent cerium salt; optionally, the cerium salt is at least one of cerium nitrate, cerium sulfate and cerium chloride.

[0020] The present invention also protects a CeMn@C catalyst with double moisture-resistant protection obtained by the preparation method.

[0021] Specifically, the CeMn@C catalyst includes crystalline MnO 2 and crystalline CeO 2 , the crystalline MnO 2 and crystalline CeO 2 The average particle size is 5 to 15 nm. Preferably, the average particle size is 8 to 12 nm; more preferably, the average particle size is 10 nm.

[0022] The use of the above CeMn@C catalyst in decomposing ozone is also within the protection scope of the present invention.

[0023] Generally, the CeMn@C catalyst can decompose ozone efficiently under the condition of an ambient humidity RH=0% to 95%; preferably, the ambient humidity RH=50% to 95%.

[0024] The CeMn@C catalyst of the present invention not only has a good ozone decomposition effect in a dry environment (RH=0%) and a low humidity environment (RH<50%), but also can utilize the hydrophobicity of carbon materials to provide a hydrophobic reaction environment for the ozone catalytic decomposition reaction and combine the moisture resistance of Ce to reduce the competitive adsorption of water molecules, thereby improving the catalytic activity of the catalyst in a high humidity environment. 2 and CeO 2 The abundant moisture-resistant active sites formed at the grain boundaries can further inhibit the competitive adsorption of water molecules at the active sites, enabling the catalyst to efficiently and stably decompose ozone in the entire humidity environment range (RH = 0% to 95%).

[0025] Compared with the prior art, the present invention has the following beneficial technical effects:

[0026] The present invention provides a method for preparing a CeMn@C catalyst with dual moisture-resistant protection, using a carbon material as a carrier, KMnO 4 and cerium salt as active component precursors, using KMnO 4 The strong oxidizing property of the carbon material undergoes a redox reaction to generate amorphous MnO 2 , while making Ce 2+ Adsorbed on the carbon material, and then calcined under specific conditions to obtain rich MnO 2 and CeO 2The CeMn@C catalyst at the grain boundary has stable and efficient ozone decomposition activity and moisture resistance, and can stably maintain more than 90% ozone decomposition activity for a long time in the full humidity range (RH=0% to 95%). BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 SEM, TEM and HRTEM images of the CeMn@C catalyst in Example 1.

[0028] Figure 2 This is the EDS image of the CeMn@C catalyst in Example 4.

[0029] Figure 3 This is a preparation flow chart of the CeMn@C catalyst in Example 1, the Ce@MnC catalyst in Comparative Example 1, and the Mn@CeC catalyst in Comparative Example 2. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0031] Example 1

[0032] A method for preparing a CeMn@C catalyst with dual moisture-resistant protection comprises the following steps:

[0033] S1. Impregnate carbon material (activated carbon) in KMnO 4 and cerium salt (cerium nitrate) in a mixed solution, fully react and then dry to remove water to obtain a catalyst precursor; wherein the mixed solution is KMnO 4 The concentration of is 0.05mol / L, the concentration of cerium nitrate is 0.05mol / L;

[0034] S2. The catalyst precursor described in S1 was calcined in an air atmosphere at 250° C. for 6 h to obtain a CeMn@C catalyst having dual moisture-resistant protection;

[0035] The catalyst precursor in S1 includes a manganese-cerium active component and a carbon carrier, and the mass ratio of the manganese-cerium active component to the carbon carrier is 1:2; the manganese-cerium active component is composed of amorphous MnO 2 and Ce 2+ The composition is in a mass ratio of 1:1.

[0036] Example 2

[0037] A method for preparing a CeMn@C catalyst with dual moisture-resistant protection comprises the same steps as those in Example 1, except that:

[0038] In step S1, the carbon material is carbon nanotubes, the cerium salt is cerium sulfate, and the KMnO in the mixed solution is 4 The concentration of is 1 mol / L, the concentration of cerium sulfate is 0.1 mol / L; the catalyst precursor in S1 includes a manganese cerium active component and a carbon carrier, and the mass ratio of the manganese cerium active component to the carbon carrier is 1:30; the manganese cerium active component is amorphous MnO 2 and Ce 2+ The composition is in a mass ratio of 10:1.

[0039] Example 3

[0040] A method for preparing a CeMn@C catalyst with dual moisture-resistant protection comprises the same steps as those in Example 1, except that:

[0041] In step S1, the carbon material is graphene, the cerium salt is cerium chloride, and the KMnO 4 The concentration of cerium sulfate is 0.05 mol / L, and the concentration of cerium sulfate is 0.01 mol / L; the catalyst precursor in S1 includes a manganese cerium active component and a carbon carrier, and the mass ratio of the manganese cerium active component to the carbon carrier is 1:20; the manganese cerium active component is amorphous MnO 2 and Ce 2+ The composition is in a mass ratio of 6:1.

[0042] Example 4

[0043] A method for preparing a CeMn@C catalyst with dual moisture-resistant protection comprises the same steps as those in Example 1, except that:

[0044] The catalyst precursor in step S1 includes a manganese cerium active component and a carbon carrier, and the mass ratio of the manganese cerium active component to the carbon carrier is 1:5; the manganese cerium active component is composed of amorphous MnO 2 and Ce 2+ The composition is in a mass ratio of 3:1.

[0045] Example 5

[0046] A method for preparing a CeMn@C catalyst with dual moisture-resistant protection comprises the same steps as those in Example 1, except that:

[0047] The calcination temperature in step S2 is 350° C., and the calcination time is 2 h.

[0048] Example 6

[0049] A method for preparing a CeMn@C catalyst with dual moisture-resistant protection comprises the same steps as those in Example 1, except that:

[0050] The calcination temperature in step S2 is 200° C., and the calcination time is 24 h.

[0051] Example 7

[0052] A method for preparing a CeMn@C catalyst with dual moisture-resistant protection comprises the same steps as those in Example 1, except that:

[0053] The calcination temperature in step S2 is 400° C., and the calcination time is 0.5 h.

[0054] Comparative Example 1

[0055] A method for preparing a Ce@MnC catalyst comprises the following steps:

[0056] S1. Impregnation of activated carbon support with KMnO 4 The catalyst precursor is obtained by drying the solution and removing the water after the reaction is completed. 4 The concentration of is 0.05mol / L, and the concentration of cerium nitrate solution is 0.05mol / L;

[0057] S2. The catalyst precursor described in S1 was calcined in an air atmosphere at 250° C. for 6 h to obtain a Ce@MnC catalyst;

[0058] The catalyst precursor in S1 includes a manganese-cerium active component and an activated carbon carrier, and the mass ratio of the manganese-cerium active component to the activated carbon carrier is 1:2; the manganese-cerium active component is composed of amorphous MnO 2 and Ce 2+ The composition is in a mass ratio of 1:1.

[0059] Comparative Example 2

[0060] A method for preparing a Mn@CeC catalyst comprises the following steps:

[0061] S1. The activated carbon support was fully impregnated with a cerium nitrate solution (0.05 mol / L), dried to remove moisture, and calcined in an air atmosphere at 250°C for 6 h; the concentration of the cerium nitrate solution was 0.05 mol / L;

[0062] S2. Add KMnO to the calcined material in S1 4 The solution (0.05 mol / L) was dried to remove moisture after the reaction to form a catalyst precursor, which was then calcined at 250°C in an air atmosphere for 6 h to obtain a Mn@CeC catalyst.

[0063] Results

[0064] The CeMn@C catalysts in Examples 1 to 7, the Ce@MnC catalyst in Comparative Example 1, and the Mn@CeC catalyst in Comparative Example 2 were respectively subjected to structural characterization and performance testing.

[0065] (1) SEM and TEM testing

[0066] The CeMn@C catalyst in Example 1 was subjected to SEM and TEM tests. The results are as follows Figure 1 As shown, Figure 1 a, 1b and 1c are the SEM, TEM and HRTEM images of CeMn@C catalyst, respectively. 2 and CeO 2 It mainly exists in the form of particles with a diameter of about 10nm, among which the lattice fringes of 0.64nm, 0.25nm, 0.24nm and 0.21nm belong to MnO 2 (001), (200), (110) and (-112) planes of (JCPDS 80-1098); the lattice fringe of 0.31 nm is attributed to CeO 2 (JCPDS 65-5923) (111) crystal plane, indicating that MnO 2 and CeO 2 Both are crystalline oxides, and the crystal planes formed by the two are rich and diverse, with obvious grain boundaries, which can increase moisture-resistant oxygen vacancies for decomposing ozone.

[0067] (2) EDS test

[0068] The CeMn@C catalyst in Example 4 was subjected to energy dispersive X-ray spectroscopy (EDS) scanning mapping, and the test results are as follows Figure 2 As shown, Figure 2 a is CeMn@C catalyst, Figure 2 b, 2c and 2d correspond to the distribution of Ce, Mn and O elements in the catalyst, respectively. It can be seen that Ce, Mn and O elements are evenly distributed, which is conducive to the formation and exposure of moisture-resistant oxygen vacancies, thereby improving the ozone decomposition performance.

[0069] (3) Preparation of CeMn@C, Ce@MnC and Mn@CeC catalysts

[0070] The schematic diagram of the preparation process of the catalyst in Example 1, Comparative Example 1 and Comparative Example 2 is as follows Figure 3 As shown, Example 1 ( Figure 3 a) is to impregnate the carbon support with KMnO 4 In a mixed solution of KMnO 4The strong oxidizing property of 4MnO causes the following redox reaction with carbon materials: 4 - +3C+H 2 O→4MnO 2 +CO 3 2- +2HCO 3 - , generating amorphous MnO 2 , and Ce 2+ adsorbed on the carbon support and then converted into crystalline MnO during the subsequent calcination process 2 and CeO 2 particles, thereby effectively controlling the MnO 2 and CeO 2 The generation order and relative position make MnO 2 and CeO 2 Adjacent to each other and forming abundant grain boundaries, exposing more moisture-resistant oxygen vacancies. Figure 3 b) First, MnO is generated on the carbon support. 2 , and then generate CeO 2 , CeO 2 It will cover the MnO 2 The surface of the present invention has limited exposure of oxygen vacancies, which is not conducive to ozone decomposition. Figure 3 c) First, CeO is loaded on a carbon carrier and calcined to form CeO 2 , then load MnO 2 , MnO 2 It will cover the CeO 2 The surface blocks the active sites, resulting in decreased ozone decomposition performance.

[0071] (4) Ozone decomposition test at different humidity levels

[0072] The catalysts in the examples and comparative examples were tested for their ozone decomposition activity.

[0073] Specific test method: The above-mentioned different catalysts are placed in glass tube reactors respectively, the amount of catalyst is 0.2g, and the reaction is carried out under normal temperature and pressure. The reaction gas (ozone) flow rate is 1L / min, air is the balance gas, the inlet ozone concentration is 40ppm, and the humidity of the reaction system is adjusted by air bubbling method (RH=0%, 15%, 50%, 95%), and then the gas concentration after the reaction is tested and analyzed for a long time (8h) using an ozone analyzer, and the ozone removal rate after long-term decomposition is recorded.

[0074] Ozone decomposition rate (%) = (Cin-Cout) / Cin×100%, where Cin is the ozone inlet concentration and Cout is the ozone outlet concentration.

[0075] Table 1 Ozone removal rate of catalysts in various embodiments and comparative examples in different humidity environments

[0076]

[0077] It can be seen from the data in Table 1 that the ozone removal rate of the CeMn@C catalyst of the present invention reaches 94% to 99% when the ambient humidity is 0%, the decomposition rate of ozone reaches 94% to 99% when the ambient humidity is 15%, the decomposition rate of ozone reaches 93% to 98% when the ambient humidity is 50%, and the decomposition rate of ozone reaches 92% to 98% when the ambient humidity is 95%. That is, the CeMn@C catalyst of the present invention has excellent moisture resistance and can achieve an ozone removal rate of more than 90% in the full humidity range (RH=0% to 95%).

[0078] In Comparative Example 1, the ozone decomposition rates of Ce@MnC catalyst at ambient humidity of 0%, 15%, 50% and 95% were 72%, 65%, 55% and 31% respectively; in Comparative Example 2, the ozone decomposition rates of Mn@CeC catalyst at ambient humidity of 0%, 15%, 50% and 95% were 61%, 50%, 43% and 28% respectively, indicating that the crystalline MnO2 was not loaded on the carbon carrier. 2 and crystalline CeO 2 The moisture resistance and ozone decomposition activity of the catalyst can be improved. The two need to form a specific structure to expose more moisture-resistant oxygen vacancies, thereby improving the ozone decomposition activity and moisture resistance of the catalyst.

[0079] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a CeMn@C catalyst with dual moisture-resistant protection, characterized in that: The following steps are involved: S1. The carbon support is immersed in a mixed solution of KMnO4 and cerium salt, and after sufficient reaction, it is dried and dehydrated to obtain a catalyst precursor; S2. The catalyst precursor in S1 is calcined in an air atmosphere to obtain a CeMn@C catalyst having dual moisture-resistant protection; The catalyst precursor in S1 includes a manganese cerium active component and a carbon carrier, and the mass ratio of the manganese cerium active component to the carbon carrier is 1:(2-30); the manganese cerium active component is composed of amorphous MnO2 and Ce 2+ Composition according to mass ratio (1-10):1; The temperature of the calcination treatment in S2 is 200-400° C., and the time of the calcination treatment is 0.5-24 hours.

2. The method for preparing the CeMn@C catalyst according to claim 1, characterized in that: The amorphous MnO2 and Ce 2+ The mass ratio is (3~6):

1.

3. The method for preparing the CeMn@C catalyst according to claim 2, characterized in that: The temperature of the calcination treatment in S2 is 250-350° C., and the time of the calcination treatment is 2-6 hours.

4. The method for preparing the CeMn@C catalyst according to claim 1, characterized in that: The concentration of KMnO4 in the mixed solution in S1 is 0.05-1 mol / L.

5. The method for preparing the CeMn@C catalyst according to claim 4, characterized in that: The concentration of the cerium salt in the mixed solution in S1 is 0.01-0.1 mol / L.

6. The method for preparing the CeMn@C catalyst according to claim 1, characterized in that: The carbon carrier in S1 is at least one of activated carbon, carbon nanotubes and graphene.

7. The method for preparing the CeMn@C catalyst according to claim 1, characterized in that: The cerium salt in S1 is at least one of cerium nitrate, cerium sulfate and cerium chloride.

8. A CeMn@C catalyst with double moisture-resistant protection obtained by the preparation method according to any one of claims 1 to 7.

9. The CeMn@C catalyst according to claim 8, characterized in that: It includes crystalline MnO2 and crystalline CeO2, and the average particle size of the crystalline MnO2 and crystalline CeO2 is 5 to 15 nm.

10. Use of the CeMn@C catalyst according to claim 8 or 9 in decomposing ozone.